2002
DOI: 10.1128/jcm.40.1.306-308.2002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Placental Malaria

Abstract: In a group of 596 delivering Ghanaian women, the sensitivities of peripheral blood thick film microscopy, ICT Malaria P.f/P.v test, and PCR in detecting microscopically confirmed placental Plasmodium falciparum infection were 42, 80, and 97%, respectively. In addition to the gross underestimation of placental malaria by peripheral blood film microscopy, submicroscopic infections were found to be a risk factor for maternal anemia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 8 publications
7
80
1
4
Order By: Relevance
“…First, placental parasitemia was determined through placental blood film instead of histological examination, a more sensitive method. [21][22][23] However, this test would have resulted in misclassification that would have biased the estimates to the null. Second, we did not have information on CD4+ counts or other clinical measures of the stage of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…First, placental parasitemia was determined through placental blood film instead of histological examination, a more sensitive method. [21][22][23] However, this test would have resulted in misclassification that would have biased the estimates to the null. Second, we did not have information on CD4+ counts or other clinical measures of the stage of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, following DNA extraction (QIAmp, Qiagen, Germany), Plasmodium species and submicroscopic infections were ascertained by nested PCR assays, 17 taking advantage of the almost complete sensitivity in detecting placentally confined Plasmodium falciparum infections. 18 Of note, in this population, MiP increased the odds of LBW by 70% and of PD by 80%. 16 From June to August 2015, we retrieved 200 of the former newborns, now aged 15 years, and invited them for a follow-up visit.…”
Section: Study Site Design and Populationmentioning
confidence: 99%
“…13,14 The detection of P. vivax and P. falciparum parasitemia by PCR, at levels undetectable by microscopy, has been reported by several authors. [15][16][17][18][19][20][21] PCR has been used for malaria diagnosis in communitybased studies carried out in Sri Lanka (one study in the Anuradhapura district and the other study in the Kurunegala and Trincomalee districts). 22,23 Neither of these studies reported any malaria positives by microscopy or PCR.…”
Section: Discussionmentioning
confidence: 99%